Effect of insulin administration on peripheral concentration of luteinizing hormone in goat - KHAN, M H; AGARWAL, S K; SHARMA, G TARU; SHANKER, U; MAJUMDAR, A C (The Indian Journal of Animal Reproduction, 2023)
Effect of exogenous administration of insulin on peripheral concentration of luteinizing hormone was studied in I 6 nondescript adult cyclic goats by collecting the blood samples at every 2 hours interval starting from onset of estrus upto 24 hours usingstandard diagnostic kit. There was no significant difference in average concentration of LH, its peak, onset of estrus to LH peakinterval and duration of LH surge between insulin treated and control groups. The results indicate that exogenous administration ofinsulin has no effect on peripheral concentration of LH.
Keywords: Insulin; luteinizing hormone; goat